Career Guidance and Counselling in Canada: Still Changing After All These Years - Bezanson, Lynne; Hopkins, Sareena; Neault, Roberta A. (Canadian Journal of Counselling and Psychotherapy, 2016)
Career counselling has held a significant place in the field of Canadian counselling. This article summarizes the history of career counselling in Canada from the early 1900s to today. Highlights illustrate a shifting focus from the concept of one job for life to managing multiple career transitions, and the consequent professionalism of career service providers through investments in product development, career practitioner competency-based training, and professional associations. Politically, responsibility for public employment and training services has shifted from federal to provincial governments. Throughout the history of Canadian career counselling, career development has clearly emerged as the bridge between managing the complexities of individual career choice and development and the changing Canadian economy and labour market realities.